Characterization and properties of silica-filled natural rubber compounds using poly(vinyl propionate)‐grafted natural rubber as compatibilizer - Ruedee Jaratrotkamjorn; Abdulhakim Masa (eXPRESS Polymer Letters, 2024)
This work presents the use of natural rubber (NR) grafted with poly(vinyl propionate) (NR-g-PVP) as an alternative compatibilizer in silica-filled NR compounds. The effects of NR-g-PVP with 10, 20 and 30% grafting on the properties of NR compounds were studied and compared with a commercial coupling agent (bis[3-(triethoxysilyl)propyl] tetrasulfide, TESPT). NR-g-PVP was compatible with silica and NR. The NR-g-PVP reduced filler-filler interactions and increased fillerrubber interactions. The crosslink density decreased with the percentage of grafting due to the steric hindrance. The compatibilization affected the physical and mechanical properties. The interactions of NR-g-PVP with silica via hydrogen bonding and subsequent vulcanization prevented undesirable filler-filler interactions and reduced the absorption of accelerators or basic materials. It caused a good dispersion of silica in the NR matrix and improved physical and mechanical properties. A 10% grafting (G10) was suitable for the compatibilizer in a silica-filled NR compound, showing the largest improvements in tensile properties, tear strength, and hardness. However, TESPT provided better properties than G10.